2022
DOI: 10.3390/molecules27206957
|View full text |Cite
|
Sign up to set email alerts
|

Random Copolymers of Styrene with Pendant Fluorophore Moieties: Synthesis and Applications as Fluorescence Sensors for Nitroaromatics

Abstract: Five random copolymers comprising styrene and styrene with pendant fluorophore moieties, namely pyrene, naphthalene, phenanthrene, and triphenylamine, in molar ratios of 10:1, were synthesized and employed as fluorescent sensors. Their photophysical properties were investigated using absorption and emission spectral analyses in dichloromethane solution and in solid state. All copolymers possessed relative quantum yields up to 0.3 in solution and absolute quantum yields up to 0.93 in solid state, depending on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 43 publications
(58 reference statements)
1
14
0
Order By: Relevance
“…Fabricated sensor elements were employed in a previously reported fluorescence recorder 36 (Figure S104). Briefly, the fluorescence recorder, equipped with a compact camera, was used to register in real time the fluorescence attenuation caused by contact of fluorescent materials with a gas mixture contaminated with the analyte vapor.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fabricated sensor elements were employed in a previously reported fluorescence recorder 36 (Figure S104). Briefly, the fluorescence recorder, equipped with a compact camera, was used to register in real time the fluorescence attenuation caused by contact of fluorescent materials with a gas mixture contaminated with the analyte vapor.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, it has been demonstrated that the optimal conditions for polymerization of styrene with 4-arylstyrenes proved to be as follows: 1.5 mol% of 2,2 0azobis(isobutyronitrile) (AIBN) in 0.5 mL of THF, the reaction temperature 80 C, the reaction time 3 h, thus providing the best yields of copolymers and the lowest polydispersity PDI. 36 The same conditions have been applied successfully for copolymerization of styrene and the corresponding N-arylaminostyrenes (3a-h) (Scheme 3). Copolymers P1-P8 were obtained in good yields, and their thermal stabilities were studied (Table 2).…”
Section: S C H E M Ementioning
confidence: 99%
See 3 more Smart Citations